Remnants of a pandemic: Possibilities of educating in the face of loss and grief - Magalhaes, Silvana; da Luz Ferreira, Ananda; Tardim, Poliane; Wanderosck Toledo, Soraia; Mengali, Priscila; Custodio da Silva, Lubia; Rodrigues de Avellar Baptista, Leomar; Messa, Luciana (Guará Journal, 2022)
This article presents the university extension course Pedagogies do Esperançar: the art of educating in the face of loss and grief, whose main objective was to provide a space for sharing knowledge  and  welcoming regarding  losses  and  mourning.  This  training prioritized  awakening  the  educators’  watchful  eye  to the protagonism and narratives of children/adolescents about their  processes  of  elaboration  of  losses. Offered  by  the  Study  and  Research  Group  on Children,  Cultures,  Education  and  Society - GEPICES/CEFET/RJ in a remote environment, the course welcomed one hundred and thirty participants, who were able to  highlight  the  need  to  talk  about individual  and  collective  pain;  about  death  and  grief. There  were  four  virtual  meetings  that dealt with different aspects related to the theme. Through theoretical  expositions,  dialogic  interactions, storytelling  and  narration, among other activities, spaces were created for acti-ve listening, that is, for the sharing of perceptions and feelings, which,  based  on the  Sociology  of  Childhood,  could  be  elabo-rated, resignified. In their testimonies, participants highlighted the importance of the proposed activities that dared to work on issues  that  contemporaneity  insists  on hiding. In  the  end,  the  perception that pain needs to be elaborated was confirmed.
Keywords: Grief; Childhoods; Children’s literature; Teacher training